KADAR NDF DAN ADF KULIT BUAH KAKAO YANG DIFERMENTASI SECARA BERTINGKAT MENGGUNAKAN Trichoderma viride DAN Saccharomyces cerevisiae (NDF and ADF Levels of Cocoa Pod Husk Gradually Fermented Using Trichoderma viride and Saccharomyces cerevisiae) - Andrik Lesmana; Ning Iriyanti; Titin Widiyastuti (Fakultas Peternakan, Universitas Hasanuddin, Makassar, 2020)
The research aimed to examine the effect of gradual fermentation using Trichoderma viride and Saccharomyces cerevisiae and its most optimal level of use on lowering NDF and ADF levels of cocoa pod husks. The experiment was conducted experimentally according to a completely randomized design (CRD) consisted of four treatments and five replications. The treatments were R0: cocoa pod husks without fermentation, R1: cocoa pod husk fermentation (T. viride 4% and S. cerevisiae 4%), R2: cocoa pod husk fermentation (T. viride 8% and S. cerevisiae 8%), R3: cocoa pod husk fermentation (T. viride 12% and S. cerevisiae 12%). Data were analyzed using analysis of variance (ANOVA) with the orthogonal polynomial test. The results showed that the gradual fermentation using T. viride and S. cerevisiae was highly significant in reducing levels of NDF and ADF of cocoa pod husks, following the equation Y = 78.926 – 0.087X – 0.092 X2 + 0.007 X3, (R2) = 93.4% and Y = 75.274 – 5.698X + 1.277 X2 – 0.073 X3, (R2) = 99.5%, respectively. In conclusion, the optimal level of using T. viride and S. cerevisiae in lowering the levels of NDF of cocoa pod husk was 9.21%, which can reduce the NDF level as much as 3.98%, while the optimal level of using T. viride and S. cerevisiae in lowering the levels of NDF of cocoa pod husks was 3.01%, which can decrease the ADF level as much as 10.01%.